2014
DOI: 10.1371/journal.pone.0087743
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Malaria and Iron Status or Supplementation in Pregnancy: A Systematic Review and Meta-Analysis

Abstract: IntroductionMalaria prevention and iron supplementation are associated with improved maternal and infant outcomes. However, evidence from studies in children suggests iron may adversely modify the risk of malaria. We reviewed the evidence in pregnancy of the association between malaria and markers of iron status, iron supplementation or parenteral treatment.Methods and FindingsWe searched MEDLINE, EMBASE, the Cochrane Central Register of Controlled Trials, the Global Health Library, and the Malaria in Pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 76 publications
1
52
0
Order By: Relevance
“…Clinicians monitored children's health statuses during sick visits and at routine visits occurring on a biweekly basis during the first 12 months of life and a monthly basis for any follow-up beyond the first year. Children's hemoglobin was measured at sick visits and during routine visits at approximately 3,6,12,18,24,30,36,42, and 48 months of age. Parasitemia by P. falciparum was determined after counting 200 leukocytes on Giemsa-stained thick blood smear of a sample collected by heel or finger prick during child visits.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinicians monitored children's health statuses during sick visits and at routine visits occurring on a biweekly basis during the first 12 months of life and a monthly basis for any follow-up beyond the first year. Children's hemoglobin was measured at sick visits and during routine visits at approximately 3,6,12,18,24,30,36,42, and 48 months of age. Parasitemia by P. falciparum was determined after counting 200 leukocytes on Giemsa-stained thick blood smear of a sample collected by heel or finger prick during child visits.…”
Section: Methodsmentioning
confidence: 99%
“…12 In addition, recent experiments have also found that hepcidin-induced iron redistribution away from hepatocytes arrests the growth of intrahepatocytic parasites and thereby prevents the occurrence of malaria superinfections. 13 Epidemiological studies lend support to these findings: pregnant women and children who are iron deficient are observed to have lower risks of malarial disease, [14][15][16][17][18] and pediatric iron supplementation has been shown to heighten the risk of both clinical and severe malaria. 19,20 In addition to malaria, elevated iron has been associated with poor prognoses in cases of bacterial and viral infections 21 and may be associated with child mortality in communities with high burdens of communicable disease.…”
Section: Introductionmentioning
confidence: 95%
“…In a systematic review of 28 observational studies, iron deficiency (indicated by circulating ferritin concentration) was found to be associated with protection against Plasmodium infection in pregnancy (Sangaré et al , 2014). …”
Section: Safety Of Antenatal Iron Interventions In Malaria‐endemic Sementioning
confidence: 99%
“…In their systematic review Sangaré et al (2014) found one single study from Asia that assessed the association between iron supplementation and P. vivax infection. In this prospective cohort study, supplementation with iron and folic acid for less than 30 days was associated with an increased risk P. vixax parasitaemia.…”
Section: Safety Of Antenatal Iron Interventions In Malaria‐endemic Sementioning
confidence: 99%
See 1 more Smart Citation